Observations about the biology of Octopus mimus (Cephalopoda: Octopoda) in the Peruvian coast - Cardoso, Franz (2004)
The Gould Octopus, Octopus mimus Gould, 1852 is widely distributed along the Peruvian coast and is target of an important artisanal fishery. The size-weight relationship in Ilo and Callao shows an allometric growth for both sexes. The females reach a spawning size at 14,3 cm of mantle length. That size was used to estimate a minimum weight of catch of 1 Kg. The diet was variable and it included crustaceans, mollusks, fish and echinoderms. Catches were six times higher during El Niño 1997– 1998 than El Niño 1982-1983. The present data is compared and discussed with those of Chile.